Komunikasi Pemasaran Wisata Halal Di Banyuwangi dan Gunungkidul - Yani Tri Wijayanti (Jurnal Komunikasi, 2021)
The concept of Halal Tourism began to be adopted in Indonesia in 2014 and is getting stronger in Indonesia following the 2016 World Halal Tourism Award in Dubai. Several regions or districts responded to this by opening halal tourism, including Banyuwangi Regency and Gunungkidul Regency. Banyuwangi Regency launched tourist area branded as ‘the first sharia beachtourism in Indonesia’, namely Santen Island Beach. Meanwhile, Gunungkidul Regency is on Torohudan Beach. The research method used is a case study. The discussion includes marketing strategy and marketing communication mix, showing the implementation of halal tourism management on Santen Island Beach was successful at the beginning with very strong branding evidence, marketing communication practices have maximized marketing strategy and communication mix. At Torohudan Beach, the community prefers the principle of ‘Muslim friendly tourism’, and in its implementation it needs support from the local government.Keywords: branding, Halal Tourism, muslim friendly tourism, sharia beach tourism